Use of transglutaminases in foods and potential utilization of plants as a transglutaminase source – Review - Fernando B. Luciano; Susan D. Arntfield (Biotemas, 2012)
Transglutaminases (TGases) are enzymes able to catalyze acyl-transfer reactions introducing covalent cross-links between proteins, peptides and primary amines. Animal TGases were the first studied and are divided in nine different groups of isoenzymes. They have a wide range of functions in the metabolism of most animal cells, and share the characteristic of being Ca2+-dependent. Microbial and plant TGases were also identified, and here is a vast heterogeneity among their amino acid sequences. Interestingly, it seems that all transglutaminases share a specific amino acid triad of Cys-His-Asp in their catalytic site, which can be found in all tertiary structures of the enzymes yet studied so far. Microbial TGases are the most widely used for food modification due to lower costs and high yields involved with their extraction and purification when compared to mammal sources. TGases are ubiquitously found in a variety of plants, and their utilization for food transformation has been proposed. However, there is only a single attempt using vegetal TGase in food systems, where apple pomace was used to improve the quality of pork meat. The transference of mammalian TGase genes to plants has also been considered and they were found to be successfully expressed in rice and tobacco leaves. These results lead to a new approach, where TGases could be literally farmed for food utilization.